ASPECTS OF PEOPLE AND CULTURE IN INDUSTRIAL TRANSFORMATION 4.0 IN BANKING INDUSTRY - Margaret Sihombing; Setyo Riyanto (SIMAK, 2022)
The purpose of this study is to analyze aspects of people and culture in the transformation of industry 4.0 in the banking industry. This research method is qualitatively descriptive with engineering design this study uses a literature approach and literature review. The transformation of Industry 4.0 in the banking industry is carried out on the Aspects of People and Culture as one of the main things. The people and culture aspects are important aspects and have the biggest point of 30% of the 5 pilar in INDI 4.0, which is an indication of the readiness of the industry to transform towards Industry 4.0. As for 3 the areas that are the focus of the Aspects of People and Culture are the Work Culture of Employees, Openness to Change, and the Development of Self Competence. With digital transformation, mindset owned by HR it can compete in the digital age and this will support banking to survive and develop into a company that excels in Industry 4.0.